PTU-015 Colonoscopic Perforation: What are the Indicators for Conservative Management?. (17th August 2016) - Derbyshire, E; Hungin, AP; Rutter, MD; ,
Abstract : Introduction: Perforation is one of the most serious adverse events associated with colonoscopy and may be managed conservatively or surgically. We have previously reported outcomes following colonoscopic perforations in the English National Health Service Bowel Cancer Screening Programme, showing that those perforations managed conservatively with bowel rest, intravenous fluids and antibiotics did not develop post perforation morbidity. 1 We therefore aimed to examine which factors could be used as indicators for conservative management. Methods: We re-evaluated our national database of 115 colonoscopic perforations admitted to hospital, including 62 patients who had surgery and 51 who didn't (two patients in whom it was unclear if surgery had occurred were excluded from the analysis). Explanatory variables examined were admission immediately following colonoscopy, the presence of abdominal pain at initial review, initial temperature, pulse rate and respiratory rate (RR). Statistical Analysis was performed using Statistical Package for the Social Sciences version 20. Fisher's exact test and pearson chi-square were used to test association between explanatory and outcome variables with a p value <0.05 considered to be significant. Results: 15.0% of the patients had none of: abdominal pain at initial review, a pulse rate > 100 beats per minute or a RR > 20 breaths per minute. 23.5% of these patients had surgery. Conclusion: The presence of abdominal pain, a pulse rate > 100 beats per minute and RR > 20 breaths per minute were significantly associated with the patient having surgery. Small numbers of patients with no abdominal pain, a pulse rate ≤ 100 beats per minute and a RR ≤ 20 breaths per minute underwent surgery. It is unclear from this retrospective data whether this surgery was actually necessary. It is possible that the absence of abdominal pain, a pulse rate ≤ 100 beats per minute and a RR ≤ 20 breaths per minute may be useful objective measures to determine whether surgery is required. Further prospective work using these indicators to guide conservative management is required. Reference: 1 Derbyshire, et al . UEG Journal October 2015;3 :1–145. Disclosure of Interest: None Declared